2011
DOI: 10.2337/dc11-1456
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the High Triglyceride-to-HDL Cholesterol Ratio to Identify Cardiometabolic Risk Factors and Preclinical Signs of Organ Damage in Outpatient Children

Abstract: OBJECTIVETo evaluate whether the high triglyceride-to-HDL cholesterol (TG-to-HDL-C) ratio is associated with cardiometabolic risk (CMR) factors and preclinical signs of organ damage in an outpatient population of white children and adolescents.RESEARCH DESIGN AND METHODSThe study population included 884 subjects (aged 6–16 years), of whom 206 (23%) were normal weight, 135 (15%) were overweight, and 543 (61%) were obese. Biochemical variables were analyzed in the whole sample, whereas homocysteine and left vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
87
3
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 24 publications
9
87
3
9
Order By: Relevance
“…One study in which this relationship was investigated in a pediatric population showed that the association between TG-to-HDL-C and ALT in obese children with NAFLD was independent of visceral adiposity and IR (6). In our study, consistent with these results, we also observed an association between TG-to-HDL-C ratio and elevated ALT.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…One study in which this relationship was investigated in a pediatric population showed that the association between TG-to-HDL-C and ALT in obese children with NAFLD was independent of visceral adiposity and IR (6). In our study, consistent with these results, we also observed an association between TG-to-HDL-C ratio and elevated ALT.…”
Section: Discussionsupporting
confidence: 82%
“…In one study based on ALT elevation for the determination of NAFLD, Di Bonito et al (6) determined a high TG/HDL-C ratio as >2 and reported that this value was useful for predicting NAFLD in clinical practice. To the best of our knowledge, no other value has been recommended for NAFLD in the pediatric age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La relación TGL/HDLc se clasificó como adecuada cuando fue <2.0 (22). Se estableció CHT cuando existió simultáneamente elevación de la CC y trigliceridemia ≥110 mg/dL (10).…”
Section: Procedimientounclassified
“…21 Se consideró elevado cuando el índice TGL/HDLc fue ≥ 2,0. 22 De acuerdo con el sexo y estadio de maduración puberal, la insulinemia e índice HOMA-IR se definieron como elevados cuando fueron ≥ al percentil 90 informado por Barja y cols. 23 Se calcularon estadísticos descriptivos de tendencia central y frecuencias absolutas y relativas.…”
unclassified